PRODUCTION POTENTIAL OF SUNFLOWER ALEY CROPPED WITH NEEM AND MELIA UNDER DRY LAND CONDITION - KRISHNAN, K. MURALI; NEERAJA, G.; SUBRAHMANYAM, M.V.R.; BHEEMAIAH, G. (Annals of Agricultural Research, 2014)
A field experiment was conducted during kharif season of 2004 and 2005 at Hyderabad, to evaluate the performance of sunflower in alley cropping system with neem and melia trees in red loamy soils of dry lands. It was observed that sole cropped sunflower gave significantly higher seed yield than that of intercropped sunflower both n pollarded neem and melia, because of competitive effect of trees. However sunflower when intercropped with pollarded neem and melia gave markedly and substantially higher growth and net returns resulting in increased B:C ratio during both the years of study than sole cropping of sunflower due to additional advantage of value added products from neem and melia trees mainly in the form of poles.